A genetic Gaussian process regression model based on memetic algorithm - Zhang, Le; Liu, Zhong; Zhang, Jian-qiang; Ren, Xiong-wei (Journal of Central South University, 2013)
Gaussian process (GP) has fewer parameters, simple model and output of probabilistic sense, when compared with the methods such as support vector machines. Selection of the hyper-parameters is critical to the performance of Gaussian process model. However, the common-used algorithm has the disadvantages of difficult determination of iteration steps, over-dependence of optimization effect on initial values, and easily falling into local optimum. To solve this problem, a method combining the Gaussian process with memetic algorithm was proposed. Based on this method, memetic algorithm was used to search the optimal hyper parameters of Gaussian process regression (GPR) model in the training process and form MA-GPR algorithms, and then the model was used to predict and test the results. When used in the marine long-range precision strike system (LPSS) battle effectiveness evaluation, the proposed MA-GPR model significantly improved the prediction accuracy, compared with the conjugate gradient method and the genetic algorithm optimization process.